A review on ceramic waste-based concrete: A step toward sustainable concrete - Ahmad Jawad; Alattyih Wael; Jebur Yasir Mohammed; Alqurashi Muwaffaq; Garcia-Troncoso Natividad (Reviews on Advanced Materials Science, 2023)
Ceramic waste (CW) has a significant negative environmental influence on the society. However, CW may benefit the environment if it is handled carefully and recycled in concrete production. Recycling CW may lessen the demand for raw materials and waste disposal, thereby preserving natural resources and lowering greenhouse gas emissions. Numerous studies discuss the possibility of CW utilization as concrete ingredients. However, data are spread, making it difficult for the reader or user to assess the benefits and drawbacks of using CW in concrete, which limits its applications. To study the benefits and drawbacks of using CW in concrete and provide the guidelines to the consumer with relevant information, a detailed review is required. Therefore, this study is carried out to collect all relevant updated information from published articles. The major topics of this article include the general history of CW, physical and chemical features, and the influence on concrete parameters including fresh, strength, elevated temperature, and cost benefits. Results indicate that CW decreased concrete flowability and strength. However, with up to 10% substitution, the results are satisfactory, and concrete can be used for a normal-strength structure. Furthermore, the review also identifies the research gaps that need to be investigated.